الشيخ محمد الأمين الشنقيطي ومنهجه في التفسير بِلمأثور - Shumsudin Yabi; Amiruddin Mohd Sobali; A. Irwan Santeri Doll Kawaid; Fadlan Othman; Akila Mamat (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
THE 6TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION (SWAT) 2019 “AL QURAN RAHMATAN LIL A’LAMIN: VISION AND CHALLENGES” 8th – 9th October 2019 / 9 – 10 Safar 1441H Hosted By : Faculty Of Quranic And Sunnah Studies, Universiti Sains Islam Malaysia (USIM)